Developing precision livestock farming tools for precision dairy farming. (1st January 2017) - Norton, T.; Berckmans, D.
Abstract: Dairy cows stay longer in production when compared with any other farmed animals. Moreover, each animal unit is of a high economical value to the farmer. Therefore, for the dairy cow and, consequently, for the farmer, it is important to detect problems as soon as possible and to take action on an individual animal level. Precision livestock farming (PLF ) systems offer a real-time monitoring and management tool for the farmer. They provide early warning to the farmer, so when something goes wrong during production, the farmer can immediately act on the information. Precision livestock farming requires real-time algorithms that are able to detect problems while the process is ongoing. To successfully develop such algorithms in an efficient way, some basic principles must be respected in the methodology being applied. This paper gives a systematic approach in using the interaction between taking field data, applying a gold standard, and using labeling techniques to develop real-time algorithms that allow real-time monitoring and management of individual cows. The paper presents the application of this process to the development of a real-time lameness detection system.